Social Media as Heterotopia: Exploring the Dynamics of Cancel Culture in the Gisella Anastasia Sex Video Scandal - Wulandari, Nur Laily; Habsari, Sri Kusumo; Susanto, Susanto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
This study examines the phenomenon of cancel culture on social media, focusing on the controversy surrounding the case of Gisella Anastasia's nude video. Utilizing Michel Foucault's heterotopia theory, this research investigates how social media platforms such as Instagram serve as heterotopias that shape new norms and challenge social rules. The study analyzes Instagram's role in cancel culture, exemplified by the Gisella Anastasia case and netizens’ responses. It explores how digital spaces blur the distinction between reality and virtuality, impacting individual freedom and identity formation. Through text and content analysis, this research uncovers power dynamics within Gisella Anastasia's Instagram accounts, @hopsindonesia, and @rananews.id, over specific time frames. The findings indicate that social media functions as a heterotopic space where netizens contest societal norms and challenge the hegemony of identities. It also shows that anonymity encourages damaging comments and perpetuates cancel culture, acting as resistance against societal norms and identities. The absence of hierarchy in social media fosters unbounded behaviors among netizens, sometimes even leading to excessive brutality.